Estimation of the Thermal Structure Beneath the Volcanic Arc of the Northern Andes by Coda Wave Attenuation Tomography - Vargas, Carlos A.; Ochoa, Luis H.; Caneva, Alexander (Frontiers in Earth Science, 2019)
In the Northern Andes, the magmatic arc rises from a broad area of active volcanism in the South, at the border between Ecuador and Colombia, to a linear north-directed trend of active and inactive volcanic cones. A ~240-km-long west-east-striking slab tear (Caldas Tear) located approx. 5.5°N creates an offset in the volcanic arc. This tear looks like a significant controller of volcanic activity: its quasi-WE structure separates inactive magmatic bodies of late Miocene age or older in the North from Quaternary magmatic activity in the South. Coda wave attenuation tomography applied on seismic waveforms recorded between 1993 and 2018 illuminates the volcanic arc, which appears as a segmented structure derived from the complex process of subduction of the Nazca and Caribbean plates under South America. The attenuation measurements are transformed into thermal measurement using standard rock physics relationships, supported by thermal estimations and geothermal gradient observations measured in wells. Active and inactive magmatic belts are associated with a range of relatively low temperatures (~640°C – ~810°C in the depth range of 25 km – 100 km), which may be a consequence of the fluid content in hydrous minerals. Along the volcanic arc, the isotherms become shallower from South to North and are interrupted by a cold structure; this structure may reflect a lateral change of the mantle viscosity that prevents the continuity of the volcanic arc. Our estimations show an irregular depth-geometry of the isotherms, probably associated with recent slip events that have perturbed the thermal state along the study area. The isotherms also deepen to the West, probably due to the subduction process of the Nazca Plate (~0 – 5°N). In some areas, the isotherms follow a trend similar to that of a thrust fault-related folding geometry, which suggests a recent process of regional perturbation. We hypothesize that the Panama Arc collision at the north and the effect that imprint the Carnegie Ridge against the continent at the South are responsible for these thermal effects. The northern anomaly suggests thickening of the lithosphere that prevents the development of the volcanic arc at the north of the Caldas Tear.